2000
DOI: 10.1038/sj.cdd.4400693
|View full text |Cite
|
Sign up to set email alerts
|

IGF-I receptor activation and BCL-2 overexpression prevent early apoptotic events in human neuroblastoma

Abstract: The type I insulin-like growth factor receptor (IGF-IR) is important for mitogenesis, transformation, and survival of tumor cells. The current study examines the effect of IGF-IR expression and activation on apoptosis in SHEP human neuroblastoma cells. SHEP cells undergo apoptosis which is prevented by IGF-I addition or overexpression of the IGF-IR (SHEP/IGF-IR cells). High mannitol treatment activates caspase-3 by 1 h in SHEP cells while caspase-3 activation is delayed by 3 h in SHEP/IGF-IR cells. Transfectio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
36
0

Year Published

2002
2002
2012
2012

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 58 publications
(40 citation statements)
references
References 77 publications
3
36
0
Order By: Relevance
“…Lack of procaspase-8 expression in Kelly, NGP and CHP-134 cells may not be sufficient to confer resistance to apoptosis induced by serum starvation, as embryonic fibroblasts obtained from CASP8À/À mice are still sensitive to serum deprivation (Varfolomeev et al, 1998). In contrast to neuroblastoma cells with low ataxin-2 expression, SH-EP cells are sensitive to apoptosis following serum deprivation (van Golen et al, 2000(van Golen et al, , 2001. The observation that MYCN expression is required for apoptosis only in confluent Tet21N cells refines and extends previous findings (Lutz et al, 1998).…”
Section: Discussionmentioning
confidence: 90%
“…Lack of procaspase-8 expression in Kelly, NGP and CHP-134 cells may not be sufficient to confer resistance to apoptosis induced by serum starvation, as embryonic fibroblasts obtained from CASP8À/À mice are still sensitive to serum deprivation (Varfolomeev et al, 1998). In contrast to neuroblastoma cells with low ataxin-2 expression, SH-EP cells are sensitive to apoptosis following serum deprivation (van Golen et al, 2000(van Golen et al, , 2001. The observation that MYCN expression is required for apoptosis only in confluent Tet21N cells refines and extends previous findings (Lutz et al, 1998).…”
Section: Discussionmentioning
confidence: 90%
“…Survival and expansion occurs in the presence of inappropriate mitogenic stimuli and disrupted apoptotic signaling. 31 It has been shown that autocrine signaling via the Type 1 insulin-like growth factor receptor (IGF1R) is a prominent mechanism by which neuroblastoma cells maintain their unregulated growth and resist the induction of programmed cell death. 9,32,33 Consistent with these data, the modulation of levels of AKT and IGF1R we have observed after exposure of cells to GA may also promote spontaneous apoptosis in neuroblastoma cells leading to the dramatic inhibition of survival/proliferation of these cells shown in Figure 2.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, IGF-I treatment or overexpression of IGF-IR prevents glucose-or mannitol-induced cell death (24,26,27). Overexpression of antiapoptotic members of the Bcl family (Bcl-2 or Bcl-xL) (25,27) or inhibition of caspases (27,28) also prevents apoptosis in neuronal cells. The PI3K pathway is critical for the antiapoptotic effect of IGF-I (29 -31).…”
Section: Igf-i Receptor (Igf-ir)mentioning
confidence: 99%
“…Flow Cytometry-The percentage of sub-G 0 DNA was measured as the percentage of apoptotic cells using flow cytometry as described previously (27). All results are expressed as the mean percentage of apoptotic cells of at least three experiments Ϯ the S.E.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation